Germ Line Mutations Associated Leukemia - He Wu, Zhan (IntechOpen, 2019)
In the current practice of modern medicine, the treatment of infectious and nutritional disorders is well established. In contrast, currently genetic disorders/diseases and cancer constitute a substantial load in the clinic. The care of genetic-based diseases and cancer has become a major task in medical practices worldwide and it is unprecedented. It will be rare for any family to be entirely free of genetic disease, therefore genetic diseases impose a huge burden upon individuals, families, and societies. Modern medicine is at the crossroads in the new genomic era with the development of more and more modern technologies. Remarkable advances have been well achieved in defining and classifying these genetic-associated diseases. The identification of the genetic landscape of germ line mutations-associated leukemia caused by either inherited gene mutations or syndromes has led to a deep understanding of leukemogenesis, recognition of clinical diagnosis, and translation into clinical practice in its specific management strategies.